Future forward : leadership lessons from Patrick J. McGovern, the visionary who circled the globe and built a technology media empire - Rifkin, Glenn (McGraw-Hill Education, 2019)
Telling the story of IDGs astonishing success and how it has been a source of inspiration for entrepreneurs all around the world, this book reveals how you can apply its people-first principles, insights, and integrity to your own organization. --